2005
DOI: 10.1007/s10329-004-0121-9
|View full text |Cite
|
Sign up to set email alerts
|

Observations on parturition and allomothering in wild capped langur (Trachypithecus pileatus)

Abstract: A birth during the day by a capped langur (Trachypithecus pileatus Blyth, 1843) was recorded at Pakhui Wildlife Sanctuary, Arunachal Pradesh, India. The birth took 43 min. Allomothering was observed 3 h after the birth. An average of 9% of daily active time was shared by four allomothers (three adults, one subadult) during the first 15 days of the infant's life. Total time allomothering was proportional to the age of the allomothers (241 min for oldest; 214 min for youngest).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 2 publications
0
24
0
1
Order By: Relevance
“…Carpenter 1964;van Lawick-Goodall 1967;Kumar et al 2005;Yao et al 2012); however, there is much variation in the response of group members to parturition (Moreno et al 1991;Takahata et al 2001). Luna and Leah received considerable attention from other mature and immature females during the week following parturition, which was manifested in grooming, peering, and proximity maintenance.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Carpenter 1964;van Lawick-Goodall 1967;Kumar et al 2005;Yao et al 2012); however, there is much variation in the response of group members to parturition (Moreno et al 1991;Takahata et al 2001). Luna and Leah received considerable attention from other mature and immature females during the week following parturition, which was manifested in grooming, peering, and proximity maintenance.…”
Section: Discussionmentioning
confidence: 95%
“…Despite this paucity of observations of parturition in the wild, there is an increasing and disproportionate body of evidence comprising various species of nonhuman primates which suggests that birth may occur in a social context more regularly than was previously thought (e.g. Dunbar and Dunbar 1974;Oppenheimer 1976;Stewart 1977;Goodall and Athumani 1980;Nigi 1982;Sekulic 1982;Chism et al 1983;Kinnaird 1990;Nakamichi et al 1992;Condit and Smith 1994;Gorzitze 1996;Kiwede 2000;Ruiz et al 2004;Dias 2005;Kumar et al 2005;Camargo and Ferrari 2007;Peker et al 2009;Turner et al 2010;Yao et al 2012;Ding et al 2013;Deluycker 2014).…”
Section: Introductionmentioning
confidence: 95%
“…Except for the behavior of licking the infant after birth, which was reported for a capped langur (Trachypithecus pileatus: Kumar et al 2005), researchers have not reported these behaviors for colobine monkeys because of the lack of observations on birth. These birth-related behaviors are similar to those described for several Macaca spp.…”
Section: Behaviors Of the Parturientsmentioning
confidence: 90%
“…In comparison with other phylogenetic groups, data on birth in colobine monkeys are even more limited. To the best of our knowledge, there is only one brief report on birth in wild capped langurs (Trachypithecus pileatus: Kumar et al 2005).…”
Section: Introductionmentioning
confidence: 96%
“…Gouzoules [1974] reported that a female M. arctoides took less than 15 min starting from the first observed signs of labour to parturition, in spite of vigorous disturbances caused by the group members, including her own son. Although vocalization by the mother [Gouzoules, 1974;Dias, 2005;Kumar et al, 2005;Turner et al, 2010], by the infant [Brandt and Mitchell, 1973;Nakamichi et al, 1992] and by both mother and infant [Ratnayeke and Dittus, 1989] has been reported in a number of primate species; none of the 3 mother-infant dyads observed in this study vocalized at any point during data collection over the complete birth period.…”
Section: Discussionmentioning
confidence: 78%